Strategi Efektif Simplifikasi Nahwu dalam Percakapan Arab pada Kelas Intensif Daurah Ramadhan - Nur Hanifansyah; Menik Mahmudah (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2025)
This study aims to explore effective strategies for simplifying Arabic grammar (nahwu) to enhance maharah kalam (speaking skills) among students participating in the intensive Daurah Ramadhan program at Pondok Pesantren Darullughah Wadda’wah (Dalwa). Using a descriptive qualitative approach, this research involved 60 takhassus students from diverse pesantren backgrounds who had prior knowledge of nahwu and sharaf but still struggled with active Arabic conversation. Data were collected through participatory observation, in-depth interviews with both teachers and students, and documentation of teaching materials and student evaluations. The data analysis employed thematic analysis, involving data reduction, categorization of themes, and interpretation of findings. To ensure data validity, triangulation methods were used, including triangulation of sources (comparing data from interviews and observations) and triangulation of methods (combining observation, interviews, and documentation). The findings reveal that simplified grammar instruction—such as recognizing the implicit meaning of "is" in jumlah ismiyyah, applying patterns with "أن", and using "قبل–بعد" structures—significantly boosted students' confidence and fluency in speaking. Moreover, the integration of mnemonic techniques, peer learning, and the jigsaw method strengthened both comprehension and communicative competence in a collaborative and contextual learning environment. This study confirms that grammar simplification is not merely a technical adjustment but a pedagogical strategy that effectively supports communicative-based Arabic language learning.